Conceptual principles of international cooperation in labour relations. (17th October 2022) - Melnychuk, Nataliia O.; Kulachok-Titova, Liudmyla V.; Sevryukov, Denys H.; Ostapenko, Yuliya O.; Shkoda, Vlada M.
Abstract : In today's world, the issue of respect for and observance of human rights in the field of labour relations is rather important. Ensuring human rights and freedoms is no longer just a domestic affair, but the goal of the entire world. The purpose of the study is to analyse the current state of Ukraine's international cooperation with foreign countries in general, and the European Union in particular. It identifies problematic aspects of implementing international standards in the field of labour protection using national legislation and solutions.